Trusted criminals - David O. Friedrichs (Thomson Higher Education, 2007)
TRUSTED CRIMINALS: WHITE COLLAR CRIME IN CONTEMPORARY SOCIETY is a comprehensive guide that covers topics ranging from the problems involved in studying white collar crimes to the principal focus of the crimes to the character of the legal and criminal justice response to the crime